THE INFLUENCE OF STUDENTS' PERCEPTIONS OF TEACHERS' SOCIAL STATUS ON THE INTEREST IN BECOMING ACCOUNTING TEACHERS - Idris, Fardini; Sahade, Sahade; Azis, Fajriani (JURNAL EDUSCIENCE, 2024)
The purpose of this research is to find out how students' perceptions of teachers' social status influence their interest in becoming an Accounting teacher, Faculty of Economics, Makassar State University. In this study, two independent variables were used, students' perceptions of teachers' social status (X) and interest in becoming an accounting teacher (Y). There were 311 participants from the Accounting Education Study Program, Faculty of Economics, Makassar State University for the 2018-2020 academic year. This research used a sample of 76 students taken through Proportionate Stratified Random Sampling. Questionnaires and written notes were used for data collection. Descriptive percentage analysis, instrument testing, and hypothesis testing were used to test the data. Based on the results of the descriptive analysis, student perceptions of teacher social status and interest in becoming an accounting teacher were included in the good category, with a percentage of student perceptions about teacher social status of 80%, and 76.8% for interest in becoming a teacher. From the results of the linear regression analysis, it was obtained that the equation model Y' = 22.952 + 0.483, which means that for every additional unit of teacher's social status value, the interest in becoming an accounting teacher increases by 0.483 units. Linear regression analysis yielded a model equation Y' = 22.952 + 0.483 which indicates that the higher the social status of a teacher, the higher the desire for a career in accounting education. Analysis of the coefficient of determination (r2) produces a value of 0.289 which indicates that students' impressions of the teacher's socio-economic position have an influence of 28.9% on their decision to pursue a career in accounting education, while the remaining 71.1% is influenced by other factors. The t-test analysis produces a significance value of 0.000 <0.05 which indicates that the student's perception of the teacher's social status variable has a significant effect on the interest in becoming an accounting.Keywords: Student Perceptions; Teacher's Social Status; Accounting Teacher